Authoritative performances of care in home exchange. (November 2022) - Hamilton, Kathy; Hewer, Paul; Tonner, Andrea
Abstract: This research examines the position of home exchange within the sharing economy. Drawing on in-depth qualitative research, we adopt the lens of authoritative performances to explore how home exchangers resolve contradictions between competing endeavours. Taking a pluralistic view, our findings have revealed that home exchangers are entrepreneurial in the meanings they attach to their homes. However, this is softened by authoritative performances of care that replace impersonal exchange with interpersonal relationships of reciprocity and mutual trust. Our findings also offer further contributions by exploring how home exchangers experience the dichotomies of familiar and unfamiliar in tourism and the absent and present host. Highlights: Home exchangers resolve contradictions through authoritative performances. The entrepreneurial aspect of home exchange meshes with its caring culture. Authoritative performances of care can replace impersonal exchange in hosting. Home exchange relies on building trust within the community. The platform becomes central when authoritative performances of care fail.